María de Jesús de la Fuente Casas de O'Higgnis - entrevista - Martínez Chapa, Paula; Hernández Garza, Magda Isabel (Universidad Autónoma de Nuevo León, 2022)
Entrevista a María de Jesús de la Fuente de O'Higgins